Analysis of SWOT-Based Employee Performance Measurement in Public Services at SAMSAT Gorontalo City - Sri Intan Aprilia; Lukman Pakaya; Ayu Rakhma Wuryandini (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to find out a SWOT analysis in measuring the performance of Gorontalo City SAMSAT employees in providing public services. The study used a quantitative approach with a sample of 39 service employees and 12 taxpayers. Data were collected through observation, interviews, documentation, and questionnaires, and analyzed using descriptive analysis, IFAS, EFAS, and SWOT. The results of the study show that both from the perspective of employees and taxpayers, the position of SAMSAT Gorontalo City is in Quadrant I (Aggressive), which reflects strong internal strength, large external opportunities, and a high level of taxpayer trust and satisfaction with service quality. The recommended strategies include optimizing service digitization, increasing human resource capacity, strengthening complaint mechanisms, and improving employees' technical competencies to realize effective, accountable, and sustainable public services.